2011
DOI: 10.1158/1078-0432.ccr-11-1209
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Pharmacokinetics and Safety of Sym004: A Synergistic Antibody Mixture Directed against Epidermal Growth Factor Receptor

Abstract: Purpose: Sym004 is a novel therapeutic antibody mixture product comprising two unmarketed monoclonal antibodies (mAb) targeting the epidermal growth factor receptor (EGFR). In previous preclinical proof-of-concept studies, Sym004 was shown to elicit superior cancer cell growth inhibition activities compared with marketed anti-EGFR mAbs. This article describes the design and results of the preclinical safety program conducted to support early clinical development of Sym004.Experimental Design: Tissue cryosectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Preclinical studies with Sym004 showed both superior induction of tumor regression as compared with other EGFR-targeting antibodies and antitumor activity in models of acquired cetuximab resistance ( 7 , 17 ). Toxicology studies in cynomolgus monkeys showed a toxicity profi le consistent with other drugs of the same class, including dermatologic and gastrointestinal events ( 19 ).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Preclinical studies with Sym004 showed both superior induction of tumor regression as compared with other EGFR-targeting antibodies and antitumor activity in models of acquired cetuximab resistance ( 7 , 17 ). Toxicology studies in cynomolgus monkeys showed a toxicity profi le consistent with other drugs of the same class, including dermatologic and gastrointestinal events ( 19 ).…”
Section: Introductionmentioning
confidence: 73%
“…The starting dose of the dose-escalation cohort was derived based on a recently published toxicology study in cynomolgus monkeys ( 19 ). Patients were enrolled sequentially, and cohorts received weekly doses of 0.4, 0.75, 1.5, 3, 6, 9, or 12 mg/kg; 1 patient in the 2 fi rst cohorts followed by 3 to 6 patients in subsequent cohorts according to the traditional 3+3 design.…”
Section: Treatmentsmentioning
confidence: 99%
“…151 Sym004, a therapeutic antibody mixture comprising several mAbs targeting EGFR, was shown to elicit superior cancer cell inhibition and has already completed safety trials. 152 Using cellular models, it was shown that Sym004 might overcome acquired resistance to cetuximab. 153 In line with this, preclinical 154 data supported tumor dependency on EGFR signaling.…”
Section: Antibodies Engaging 2 Non-overlapping Epitopes Of Her3mentioning
confidence: 99%
“…There are at least eight different examples of antibody mixtures that are currently in clinical development [1]. These antibody mixtures may provide advantages over antibody monotherapy because the individual antibody components present in the mixture may complement each other to target the diseases (Table 1) [17]. For example, Xoma is developing an antibody mixture containing three antibodies to target and neutralize the toxin from botulism poisoning [15][16][17].…”
mentioning
confidence: 99%
“…For example, Xoma is developing an antibody mixture containing three antibodies to target and neutralize the toxin from botulism poisoning [15][16][17]. Xoma 3AB, which is a lyophilized formulation of three different antibodies in equimolar proportions directed against three distinct domains on the BoNT/A neurotoxin protein, is an example of an antibody mixture against a single antigen [15][16][17].…”
mentioning
confidence: 99%